Genetic burden of common variants in progressive and bout-onset multiple sclerosis. (June 2014) - Sorosina, Melissa; Brambilla, Paola; Clarelli, Ferdinando; Barizzone, Nadia; Lupoli, Sara; Guaschino, Clara; Osiceanu, Ana Maria; Moiola, Lucia; Ghezzi, Angelo; Coniglio, Gabriella; Patti, Francesco; Mancardi, Gianluigi; et al.
Background: The contribution of genetic variants underlying the susceptibility to different clinical courses of multiple sclerosis (MS) is still unclear. Objective: The aim of the study is to evaluate and compare the proportion of liability explained by common SNPs and the genetic burden of MS-associated SNPs in progressive onset (PrMS) and bout-onset (BOMS) cases. Methods: We estimated the proportion of variance in disease liability explained by 296, 391 autosomal SNPs in cohorts of Italian PrMS and BOMS patients using the genome-wide complex trait analysis (GCTA) tool, and we calculated a weighted genetic risk score (wGRS) based on the known MS-associated loci. Results: Our results identified that common SNPs explain a greater proportion of phenotypic variance in BOMS (36.5%±10.1%) than PrMS (20.8%±6.0%) cases, and a trend of decrease was observed when testing primary progressive (PPMS) without brain MRI inflammatory activity ( p = 7.9 × 10 −3 ). Similarly, the wGRS and the variance explained by MS-associated SNPs were higher in BOMS than PPMS in males (wGRS: 6.63 vs 6.51, p = 0.04; explained variance: 4.8%±1.5% vs 1.7%±0.6%; p = 0.05). Conclusions: Our results suggest that the liability of disease is better captured by common genetic variants in BOMS than PrMS cases. The absence of inflammatory activity and male gender further raise the difference between clinical courses.